Cryoatomic force microscopy of filamentous actin. - Shao, Z (2000)
Cryoatomic force microscopy (cryo-AFM) was used to image phalloidin-stabilized actin filaments adsorbed to mica. The single filaments are clearly shown to be right-handed helical structures with a periodicity of approximately 38 nm. Even at a moderate concentration ( approximately 10 microg/ml), narrow, branched rafts of actin filaments and larger aggregates have been observed. The resolution achieved is sufficient to resolve actin monomers within the filaments. A closer examination of the images shows that the branched rafts are composed of up to three individual filaments with a highly regular lateral registration with a fixed axial shift of approximately 13 nm. The implications of these higher-order structures are discussed in terms of x-ray fiber diffraction and rheology of actin gels. The cryo-AFM images also indicate that the recently proposed model of left-handed F-actin is likely to be an artifact of preparation and/or low-resolution AFM imaging.